Exogenous 24-epibrassinolide promoted growth and nitrogen absorption and assimilation efficiency of apple seedlings under salt stress - Yu, Bo; Wang, Laiping; Guan, Qiuzhu; Xue, Xiaomin; Gao, Wensheng; Nie, Peixian (Frontiers in Plant Science, 2023)
High salinity significantly hampers global agricultural productivity. Plants typically undergo lower nitrogen utilization efficiency (NUE) under salt stress. As an active byproduct from brassinolide biosynthesis, 24-epibrassinolide (EBR) is involved in regulating the stress-treated plant N absorption and assimilation. However, the exogenous EBR application effects’ on N absorption and assimilation in apple exposed to the salt-stressed condition remains unclear. Herein, we sprayed exogenous EBR (0.2 mg L-1) on apple dwarf rootstock (M9T337) seedlings (growing hydroponically) under salt (NaCl) stress in a growth chamber. We analyzed the seedling development, photosynthesis and its-mediated C fixation, N (NO3−) absorption and assimilation in reponse to exogenous EBR application under salt stress. The findings demonstrated that NaCl stress greatly hampered seedlings’ root growth and that exogenous EBR application obviously alleviated this growth suppression. Exogenous EBR-treated plants under NaCl stress displayed the more ideal root morphology and root activity, stronger salt stress tolerance and photosynthetic capacity as well as higher C- and N-assimilation enzyme activities, NO3− ion flow rate and nitrate transporter gene expression level than did untreated plants. Furthermore, the results of isotope labeling noted that exogenous EBR application also enhanced 13C-photoassimilate transport from leaves to roots and 15NO3− transport from roots to leaves under NaCl stress. Our findings imply that exogenous EBR application, through strengthening photosynthesis, C- and N-assimilation enzyme activities, nitrate absorption and transport as well as synchronized optimizing the distribution of seedlings’ C and N, has a fundamental role in improving NUE in apple rootstock seedlings under salt stress.